Determination of Boiler Building Verticality in Power Plant Construction using Terrestrial Laser Scanner (TLS) - Mohamad Bagas Setiawan; Yulaikhah Yulaikhah; Ruli Andaru (Jurnal Geospasial Indonesia, 2019)
Nowadays, Indonesian government is focusing on build up infrastructures, especially power plant infrastructures to fulfil electrical energy needs. One of the power plants that will be built up is Waai power plant which located on Waai village, Maluku Province. Waai power plant had been postponed since 2014. In order to build this power plant, the advisability of the building needed to be checked from its verticality level. This level was determined by Terrestrial Laser Scanner (TLS). The TLS’s point clouds were registered using two methods, there are target to target and cloud to cloud methods. There are 65 beams on the power plant boiler building, but only 31 beams that used as the samples to assign the verticality of the boiler construction. The verticality level was set on the X-axis, Y-axis, and the resultant of the X and Y axis by using Pythagoras theorem after the bottom and top coordinates from each beam was determined. The Queensland Building and Construction Admission Standards and Tolerances Guide 2016 was used as tolerance of verticality level. The result of the verticality calculation presented on the X-axis consisted from -0ᵒ 1’ 26,678” to 0ᵒ 4’ 11,778” with the average was 0ᵒ 1’ 40,820” and major direction pointed the positive axis. On the Y-axis, the average was -0ᵒ 0’ 45,772” with -0ᵒ 3’ 33,345” as minimum and 0ᵒ 1’ 25,319” as the maximum and the major direction went to the negative axis. The verticality on the resultant of X and Y axis was from 0ᵒ 0’ 45,225” until 0ᵒ 4’ 15,674” with the average was 0ᵒ 2’ 27,057” and the direction was to the southeast. After the verticality number was compared with the tolerance, the verticality level was smaller than the standard on each beam. From the result, we can conclude that the boiler building on the Waai power plant can be categorized safe to reconstruct.